2015
DOI: 10.1108/itp-10-2014-0232
|View full text |Cite
|
Sign up to set email alerts
|

Information disclosure of social media users

Abstract: 2Information disclosure of social media users: does control over personal information, user awareness and security notices matter? Abstract Purpose -Our study bridges the gap in the existing literature by exploring the antecedents of information disclosure of social media users. In particular, the paper investigates the link between information disclosure, control over personal information, user awareness and security notices in the social context, all of which are shown to be different from existing studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 64 publications
2
33
0
3
Order By: Relevance
“…Various studies have been conducted to study check-in behavior under different perspectives like privacy [27,28], gender differences [29], and geographical distances [30]. Research [31,32] has found that the capacity of sharing information with millions of users is a simple method to meet with friends, make new friends, experience new things, and manage one's identity.…”
Section: Related Workmentioning
confidence: 99%
“…Various studies have been conducted to study check-in behavior under different perspectives like privacy [27,28], gender differences [29], and geographical distances [30]. Research [31,32] has found that the capacity of sharing information with millions of users is a simple method to meet with friends, make new friends, experience new things, and manage one's identity.…”
Section: Related Workmentioning
confidence: 99%
“…Various studies have been conducted to study check-in behavior under different perspectives such as privacy [32,33], gender differences [34], and geographical distances [7]. However, Benevenuto et al [35] presented an analysis of user workloads in online social networks to study opportunities for better interface design, richer studies of social interactions, and improved design of content distribution systems.…”
Section: Related Workmentioning
confidence: 99%
“…People are increasingly using online social networks (or social media 1 ), such as Facebook, Twitter and LinkedIn. However, information-sharing by social-network users can result in violations of privacy (Garg & Camp, 2015) and security (Benson, Saridakis & Tennakoon, 2015). For example, a user whose contact details have been revealed may become the subject of harassment in a deliberate, repeated, and hostile manner (cyber-bullying) or become a potential victim of identity theft.…”
Section: Introductionmentioning
confidence: 99%